KONTRIBUSI KELENTUKAN OTOT PINGGANG TERHADAP KEMAMPUAN HEADING PEMAIN SEPAKBOLA SMA N 2 KABUPATEN KAUR - Heldi, Heldi; Sumantri, Ajis; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the contribution of waist muscle flexibility to heading abilities in SMA N 2 Kabupaten Kaur football players. This type of research is correlational research. The research sample is 20 people. The instruments used in this study were the flexion of the trunk test and the heading ability test in soccer games. Where the results of waist muscle flexibility as many as 2 people (10%) have a Good category. As many as 10 people (50%) have the Enough category. As many as 6 people (30%) had the Poor category and 2 people (10%) had the Very Poor category and the results of heading ability as many as 1 person (5%) had the Very Good category. As many as 9 people (45%) have a Good category. As many as 6 people (30%) have the Adequate category and as many as 4 people (20%) have the Poor category. Based on the results of the study above, there is Flexibility of the Waist Muscles Against Heading Ability of 68.00%.